Triagem e diagnóstico de TEA: perspectivas de médicos atuantes em municípios paulistas - Bianchi, Bruna (Universidade Federal de São Carlos, 2021)
Considering the advance of knowledge about Autistic Spectrum Disorder (ASD), the changes that have occurred in the characterization of people with autism according to the Diagnostic and Statistical Manual of Mental Disorders (DSM), the International Statistical Classification of Diseases and Related Problems Health (CID) and the emergence of new diagnostic tools, questioned what procedures physicians specialized in pediatrics, neuropediatrics and/or neurology employ to perform better-informed diagnoses in the investigation of ASD. Therefore, this study aimed to: Identify the procedures used by pediatricians, neurologists and neuropediatricians to screen and diagnosis of children with Autism Spectrum Disorder (ASD); Describe the training and experience of these professionals in carrying out diagnoses of children with autism/ASD; Identify the criteria that these doctors use for early diagnosis; and Identify the knowledge of professionals about ASD. The design was descriptive with a mixed approach. The participants were professionals graduated in the medical course, specialized in pediatrics, neurology or neuropediatrics who practice the profession in the interior of the state of São Paulo. The professionals were identified in the lists of specialties available for online consultation on the websites of health plans and a website of medical schools in Brazil, selecting those from the interior of São Paulo. With the lists in hand, the professionals were contacted via email or telephone. The questionnaire was applied online via Google Forms. The study had descriptive statistical analysis. Nine pediatricians participated in the research, one specialized in neurology and neuropediatrics. The results showed that for physicians, the characteristics of ASD are present in social communication, motor movements, the use of stereotyped or repetitive objects or speech, and, in some cases, persistence in social interaction. Most doctors do not work with a multidisciplinary team and those who claimed to work said they had the support of the Occupational Therapist and the Speech-Language Pathologist as the main team members. As for the resources, the most used manual and/or booklet were the ICD-10 and the DSM-V, which are the most updated. Besides these, they use the instruments: M-CHAT, CARS and the ADOS or ADOS-2. Regarding the procedure for making the diagnosis, the physicians informed that they consult other specialists, with the neuropediatrician being the most indicated, in addition to relying on the child's family help, tests, anamnesis, behavioral assessment. Six participants informed that according to their experiences, the diagnosis is being early and is completed by the child's 3 years and 11 months of age. It is concluded that physicians have up-to-date information on the characterization of ASD, know the procedures to be performed to make a diagnosis, and are doing it early.
Screening and diagnosis of ASD: perspectives of doctors working in cities in São Paulo
Keywords: Educação especial; TEA; Crianças; Diagnóstico; Médicos; Special education; ASD; Children; Diagnosis; Physicians; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM